The Unforgettable Jakarta in Imaginary City (2017) - Annisa Fhadilla; Delvi Wahyuni (Universitas Negeri Padang, 2022)
Jakarta in Imaginary City by Rain Chudori (2017) presents how psychogeography theory shows that environmental effects can influence people's ways of thinking, behaviour and emotions. This study aims to prove how Jakarta as a setting of imaginary city affects the emotions and behaviour of characters. Therefore, there are four key words in this novel Dérive, Flâneur, Sense of place, and Place Attachment. The method used in this research is descriptive qualitative by applying the theory of Psychogeography. The use of the concept is based on the interpretation of the text and in the context of the novel. This analysis also uses many fictional elements such as plot, character, conversation and setting to reveal the meaning contained in the novel. The result of the research shows that there are three keywords that can be proven in this novel based on psychogeography theory.